Estrategias para que el uso del internet no interfiera la comunicación en los hogares de la ciudadela La Inmaculada de la ciudad de Loja - Rivas Godos, Andrea del Cisne (2015)
Family communication should be the starting point in a home, the dialogue in homes, currently conceptualization is interrupted by the presence of several factors, one of them the inappropriate use of Internet. Convinced of the influence of the Internet on communication interference Household Citadel Immaculate did a survey for the preparation of the Thesis Project which formed it by interviewing 12 people heads of households belonging to that citadel where it was found that 6 families, corresponding to 50% of all respondents stated that use of the internet interferes with communication of each of the members of the family; this became the foundation to undertake research of the problem: What are the strategies for the use of Internet communication does not interfere in the homes of the citadel's immaculate city of Loja? Then the research process was conducted in the period from March to June 2014, in the aforementioned citadel which corresponds to the city, county and province of Loja, where he worked with 100 families of the citadel, a number that was then removed to apply the formula for the population, and several interviews were carried out directly with President Holger Ojeda, who became an empirical guide for the information that was later used in the development and implementation of the proposed alternative. After the analysis and discussion of information, process that allowed to formulate conclusions and recommendations proceeded. Then it was found in a high percentage that the internet communication interferes homes. All this became an justification to conduct a seminar-workshop to meet the inhabitants of the citadel research results and enable them to give adequate internet use.